2000
DOI: 10.1086/302901
|View full text |Cite
|
Sign up to set email alerts
|

The Ile198Thr and Ala379Val Variants of Plasmatic Paf-Acetylhydrolase Impair Catalytical Activities and Are Associated with Atopy and Asthma

Abstract: The platelet-activating factor (PAF) represents a phospholipid with complex biological functions, including involvement in inflammatory processes. The degrading enzyme PAF acetylhydrolase (PAFAH) represents a candidate for asthma and other atopic diseases. Two loss-of-function mutations of PAFAH are associated with severe asthma in Japanese individuals. Our aim was to look for further PAFAH variants in white populations, their possible association with atopic and asthmatic phenotypes, and their functional impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 38 publications
5
109
0
2
Order By: Relevance
“…16 I198T and A379V were associated with atopy and asthma, probably due to a decrease in the affinity of pPAF-AH for substrate. 17 However, the frequencies and the effects on atherosclerosis of these variants in the Japanese have not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…16 I198T and A379V were associated with atopy and asthma, probably due to a decrease in the affinity of pPAF-AH for substrate. 17 However, the frequencies and the effects on atherosclerosis of these variants in the Japanese have not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] On the basis of experimental findings and studies of gene expression, IL17F is a good positional candidate gene for asthma. We sequenced IL17F to characterize polymorphisms in this gene.…”
mentioning
confidence: 99%
“…9, 10 The prevalence of 279FF was reported to be 0.4%, 1.2%, and 3% in the Chinese, Korean, and Japanese populations, respectively, 11-13 but this variant is rare in non-Asian populations. 14 In a recent meta-analysis including 79,036 participants in 32 prospective studies, Lp-PLA2 activity and mass each showed continuous associations with risk of CAD, similar in magnitude to that with non-high-density lipoprotein cholesterol and systolic blood pressure. 15 In addition, it has been shown that Lp-PLA2 is an independent predictor of cardiovascular disease (CVD) that is not influenced by traditional risk factors or other inflammatory markers such as high-sensitivity C-reactive protein (hs-CRP).…”
Section: Discussionmentioning
confidence: 94%